2014
DOI: 10.1002/2014jd021781
|View full text |Cite
|
Sign up to set email alerts
|

Advanced meteor radar installed at Tirupati: System details and comparison with different radars

Abstract: An advanced meteor radar, viz, Sri Venkateswara University (SVU) meteor radar (SVU MR) operating at 35.25 MHz, was installed at Sri Venkateswara University (SVU), Tirupati (13.63°N, 79.4°E), India, in August 2013 for continuous observations of horizontal winds in the mesosphere and lower thermosphere (MLT). This manuscript describes the purpose of the meteor radar, system configuration, measurement techniques, its data products, and operating parameters, as well as a comparison of measured mean winds in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…The background wind contains both gravity waves and tides. It is clear from the figures that both zonal and meridional winds at these two locations show strong similarities, except that the Rothera winds are weaker than those from KSS MR at higher altitudes as expected (Rao et al, 2014). Since, the two radars are separated only by 8 o latitude, significant difference in winds is not expected (Dowdy et al, 2004), which is confirmed in these figures.…”
Section: Mesospheric Mean Wind Structure During 2010supporting
confidence: 76%
See 2 more Smart Citations
“…The background wind contains both gravity waves and tides. It is clear from the figures that both zonal and meridional winds at these two locations show strong similarities, except that the Rothera winds are weaker than those from KSS MR at higher altitudes as expected (Rao et al, 2014). Since, the two radars are separated only by 8 o latitude, significant difference in winds is not expected (Dowdy et al, 2004), which is confirmed in these figures.…”
Section: Mesospheric Mean Wind Structure During 2010supporting
confidence: 76%
“…The radar operates with a transmitting power of 25 kW at a frequency of 1.98 MHz (Hibbins et al, 2007) and provides winds in the mesosphere and lower thermosphere at 4 km altitude resolution every hour and these data were re-sampled to 2 km height resolution. The winds measured by a MF radar are usually in agreement with those measured by a meteor radar up to an altitude of ~94 km, above which a MF radar tends to underestimate the winds compared to those observed by a meteor radar (Manson et al, 2004;Portnyagin et al, 2004;Rao et al, 2014). In the present study we made use of winds at 82 km to characterize the mesosphere response to the 2010 minor SSW.…”
Section: Mesospheric Radar Datamentioning
confidence: 51%
See 1 more Smart Citation
“…8(b), the data acquisition rate of the high mode is mainly concentrated at heights of 66-86 km with a maximum up to 17%, which is lower than that of the low and middle mod. It is because the winds in the mesosphere are only available during the daytime (8 LT-16 LT) in the D region (due to insufficient D region ionization during nighttime) (Rao et al, 2014). Actually, if the time range is limited in the daytime, the maximum data acquisition of the high mode is more than 50%.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Two reasons might be resulting in the discrepancies between the observations of the two radars. The first one is the localized gravity waves, tides or planetary waves could make the differences between them (Rao et al, 2014;Ratnam et al, 2001). The second is that the low data acquisition rate of the Wuhan MST radar in the mesosphere could lead to the fluctuations of the daily mean data, which shows the sudden changes of the MST radar measurements at some heights.…”
Section: Mesospheric Observationmentioning
confidence: 99%